Comparison of Febuxostat and Allopurinol in the Treatment of Patients with Chronic Kidney Disease Stage 3∼5 with Hyperuricemia - Zhimin Liao; Lei Xu; Bo Wan; Liping Wang; Chengzhi Zhao; Gang Wu; Rui Xie (Emergency Medicine International)
Objective. To compare the efficacy of febuxostat and allopurinol in the treatment of chronic kidney disease (CKD) at stages 3∼5 with hyperuricemia. Methods. A total of 100 patients with stage 3 to 5 CKD with hyperuricemia in our hospital from July 2018 to December 2019 were selected and divided into the control group (n = 50) and the experimental group (n = 50) according to the random number expression method, the control group on the basis of conventional treatment with allopurinol treatment, the experimental group based on conventional treatment using the febuxostat be treatment. The clinical efficacy, incidence of adverse reactions, and renal function indexes, blood urea nitrogen (BUN), serum creatinine (Scr), serum sodium (Na), serum potassium (K), and serum uric acid (UA) before and after treatment were compared between the two groups. Results. The total effective rate of the experimental group and the control group was 82.00% and 78.00%, respectively, with little difference (P>0.05); compared with before treatment, BUN, Scr, and UA of the two groups were decreased (P<0.05); and the degree of decline in the experimental group was significantly greater than that in the control group (P<0.05); the incidence of adverse reactions in the control group was 22.00%, which was significantly higher than that in the experimental group (10.00%) (P<0.05). Conclusion. Compared with allopurinol, febuxostat can improve renal function, reduce UA levels, and reduce the occurrence of complications, with high safety, which is worthy of further clinical promotion.